THE TRANSFORMATION OF CONSTITUTIONALISM IN THE NATIONAL CRIMINAL CODE: HARMONIZING CRIMINAL OFFENSES WITH HUMAN RIGHTS PROTECTION IN INDONESIA - Ian Aji Hermawan (Yayasan Adra Karima Hubbi, 2026)
This research analyzes the urgency of synchronizing the national criminal codification under Law Number 1 of 2023 with constitutional principles and human rights protection in Indonesia. Employing a normative legal method utilizing statutory and conceptual approaches, the study evaluates the vertical synchronization between new criminal norms and the 1945 Constitution. The findings reveal a significant constitutional paradox: the expansion of criminal offenses, particularly those protecting state dignity and formally recognizing living law, risks narrowing democratic spaces and undermining fundamental legal certainty. Specifically, the protection of public officials' dignity potentially distorts popular sovereignty, while the integration of unwritten customary law threatens the strict principle of legality. Consequently, this study concludes that constitutionalism must serve as the ultimate compass for criminal law enforcement to prevent authoritarian regression. It strongly recommends the urgent harmonization of derivative regulations, rigorous judicial oversight by the Constitutional Court, and enhanced constitutional literacy among law enforcement officials to prevent the abuse of state punitive power and safeguard civil liberties.